Exploring gender differences in the relationship between gut microbiome and depression - a scoping review - Niemela, Leila; Lamoury, Gillian; Carroll, Susan; Morgia, Marita; Yeung, Albert; Oh, Byeongsang (Frontiers in Psychiatry, 2024)
Background: Major depressive disorder (MDD) exhibits gender disparities, and emerging evidence suggests the involvement of the gut microbiome, necessitating exploration of sex-specific differences. Methods: A review was conducted, encompassing a thorough examination of relevant studies available in Medline via Ovid, Embase via OvidSP, CINAHL, and PsycINFO databases from their inception to June 2023. The search strategy employed specific keywords and Medical Subject Headings (MeSH) terms tailored to major depressive disorder in women, encompassing unipolar depression, depressive symptoms, and dysbiosis. Results: Five studies were included. Among the four studies, alterations in alpha (n=1) and beta diversity (n=3) in the gut microbiome of individuals with MDD were revealed compared to controls. Gender-specific differences were observed in four studies, demonstrating the abundance of specific bacterial taxa and highlighting potential sex-specific implications in MDD pathophysiology. Correlation analyses (n=4) indicated associations between certain bacterial taxa and the severity of depressive symptoms, with varying patterns between males and females. Studies (n=3) also highlighted promising findings regarding the potential utility of microbial markers in diagnosing MDD, emphasizing the crucial role of sex stratification in understanding the disease pathophysiology. Conclusions: The findings underscore the importance of recognizing gender-specific differences in the composition of the gut microbiome and its relationship with MDD. Further comprehensive robust studies are required to unravel the intricate mechanisms underlying these disparities.